Purification, characterization and probiotic proliferation effect of exopolysaccharides produced by Lactiplantibacillus plantarum HDC-01 isolated from sauerkraut - Yu, Liansheng; Ye, Guangbin; Qi, Xintong; Yang, Yi; Zhou, Bosen; Zhang, Yunye; Du, Renpeng; Ge, Jingping; Ping, Wenxiang (Frontiers in Microbiology, 2023)
In this study, an exopolysaccharide (EPS)-producing strain of Lactiplantibacillus plantarum HDC-01 was isolated from sauerkraut, and the structure, properties and biological activity of the studied EPS were assessed. The molecular weight of the isolated EPS is 2.505 × 106 Da. Fourier transform infrared spectrometry (FT-IR) and nuclear magnetic resonance (NMR) results showed that the EPS was composed of glucose/glucopyranose subunits linked by an α-(1 → 6) glycosidic bond and contained an α-(1 → 3) branching structure. X-ray diffraction (XRD) analysis revealed the amorphous nature of the EPS. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) showed that the isolated EPS had a smooth and compact surface with several protrusions of varying lengths and irregularly shaped material. Moreover, the studied EPS showed good thermal stability, water holding capacity, and milk coagulation ability and promoted the growth of probiotics. L. plantarum EPS may be used as prebiotics in the fields of food and medicine.